Architectural Semiotics: Reading Symbolic Meanings in Modern Building Design - Ayub Muktiono (KENDALI: Economics and Social Humanities, 2023)
Semiotics, as the study of signs and meaning, is a theoretical basis for analyzing the symbolic meanings hidden in architectural elements. This research aims to explore the meaning of symbols contained in modern building design through an architectural semiotic approach. In this research, a qualitative approach was used with descriptive methods. The results of research in architectural semiotics reveal that modern building design can be understood as a symbolic language that carries deep meaning. Through analysis of design elements, such as geometric shapes, innovative materials, and use of space, this research identifies symbols that communicate certain values, aesthetics, and concepts. Involvement of the user's cultural, social context, and subject experience helps refine symbolic interpretation, creating a more contextual and relevant understanding. Overall, architectural semiotics research contributes to constructing a systematic and in-depth picture of symbolic language in modern building design, opening a window for a broader understanding of the complex role of design elements in imbuing the meaning of contemporary architecture.